Hubungan faktor motivasi, gaya kepimpinan dan persekitaran kerja terhadap tekanan kerja di kalangan Jurutera Awam, Cawangan Jalan, Jabatan Kerja Raya - Mohd Zaire, Omar (2014)
This study aims to examine the relationship and influence factors of motivation, leadership style, working in influence occupational stress. This study is made at the branch roads, public works Department Headquarters where the target involved is the civil engineer grade J41 until J54. A total of 88 questionnaires were distributed to all target respondents. Of the total amount, a total of 81 was raised and only 80 only used for further analysis. Data analysis made using "Statistical Package for Social Science (SPSS) version 17.0". Among the types of analysis were Perason correlation test, regression test, t-test and one-way ANNOVA test. Pearson correlation test showed a significant relationship between all independent variables towards occupational stress . Multiple regression test shows the motivational factors and environmental work is seen to influence occupational stress. The t-test and one-way ANNOVA indicated there were no significant differences between gender, work experience, job grade with occupational stress.